O processo de reflexão orientada na formação continuada de professores e a promoção de práticas didático-pedagógicas com orientação CTS/PC - Santos, Thayná Souza dos (2020)
With the transformations of society, it became necessary a series of changes that involve determinants of an individual's quality of life whether environmental, technological or economic, in which teacher training is a strong ally in the search for the survival of this, since educational environments are the stage of development and citizen performance. With this work, this work describes Formative Processes and Principles that shaped the Oriented Reflection Process used as a framework for the institution of Scientific Literacy, having as its starting point the concern with a model of continuing training that really intervenes in scientific education in a contextualized way, privileging a space for the discussion and study of social themes with political, economic and environmental aspects.Therefore, this study aimed to investigate how a Oriented Reflection Process can, in fact, promote didacticpedagogical practices aimed at Scientific Literacy. The formative action was implemented in seven meetings, distributed in four methodological dimensions arising from the relationship between the Oriented Reflection Process and the Formative Principles: I. Reflection in Science teaching in initial and continuing education on the Scientific Literacy perspective: the perceived; II. Perspectives on pedagogical and didactic needs in science teaching for scientific literacy: doing so; III. Teaching practices as a basic and continuous training tool: action; IV. Considerations on didactic-pedagogical practices promoting Scientific Literacy: autonomy,where data were collected through interviews, audio recordings and transcription of participants' statements, thus having qualitative characteristic, having as public public teachers of sciences of the public network of the state of Sergipe, participants of the Institutional Program of Initiation Scholarships to Teaching and Pedagogical Residency, calling itself a case study. Being analyzed through Content Analysis, by categories defined a posteriori:a. Conceptions on science teaching to promote Scientific Literacy; b. Training elements necessary for (re) formulation of teaching practices with Science-TechnologySociety guidance to promote Critical Thinking; c. Critical-reflective action on practices in the science teaching process for LC; d. The perceive-to-act to build didactic-pedagogical autonomy.Data analysis showed that the Oriented Reflection Process is a formative strategy of great relevance for organizing practices that value an education focused on scientific, technological and social aspects, also presenting itself as a potential tool for the construction of didactic-pedagogical autonomy, because teachers who demonstrated appropriation of science/technology/society interrelationships in a complexified way in the theoretical debates revalidated is in the stage of organization of activities whose intention is to promote Critical Thinking based on a Science developed in and by society.